Semi-transparent PV and double-glazed windows for heat reduction and electricity generation: a study for office buildings in tropical climate - Marhama Jelita,; Miftahuddin,; Suhaimi,; Habibis Saleh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aims to develop a methodology for the evaluation of the potential energy saving and energy generation of semi-transparent PV and double-glazed window in Indonesia office buildings. The evaluation is based on Comsol software. The heat transfer equations for the inside the enclosure between the glass have been constructed according to the natural convection equation. The simulations were accomplished for four orientations from January until December and compared to a single-glazed window. The results show that it is possible to reduce the energy consumption for artificial lighting and air-conditioning using appropriate control systems and furthermore to generate electricity using semi-transparent photovoltaic panels in windows. The use of semi-transparent PV and double-glazed window has proven to be more effective in reducing heat transfer in buildings and generate electricity. East-facing double-glazed windows produce the most electricity, approximately 341 kWh.